2018
DOI: 10.1016/j.juro.2018.02.2217
|View full text |Cite
|
Sign up to set email alerts
|

MP68-13 THE NEXT GENERATION: IN VITRO COMPARISON OF A NOVEL SINGLE-PROBE DUAL-ENERGY LITHOTRIPTER TO CURRENT DEVICES

Abstract: Percutaneous nephrolithotomy (PCNL) is considered the standard for large renal stones.Previous evaluations have found that gaining initial access to the collecting system represents the most difficult portion of PCNL procedures. We sought to broadly assess the experience of urology residents in the United States (USA) and evaluate for factors associated with increased comfort in percutaneous access.METHODS: Program representatives from each the 137 Accreditation Council for Graduate Medical Education (ACGME) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Preliminary research into the Trilogy concluded that it was more efficient at stone clearance when compared to the ShockPulse SE and LithoClast Select lithotripter models [6,7]. Moreover, initial in vitro studies in animal bladders had deemed it to be safe for usage [8].…”
Section: Swisslithoclast Trilogymentioning
confidence: 99%
“…Preliminary research into the Trilogy concluded that it was more efficient at stone clearance when compared to the ShockPulse SE and LithoClast Select lithotripter models [6,7]. Moreover, initial in vitro studies in animal bladders had deemed it to be safe for usage [8].…”
Section: Swisslithoclast Trilogymentioning
confidence: 99%